Efektivitas Program E-Kios Sebagai Bentuk Pelayanan Publik di Kecamatan Benowo Kota Surabaya - Cahyani, Dwinda Rachma; Oktariyanda, Trenda Aktiva (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
One of the indicators of service effectiveness in Benowo District, Surabaya City, is the implementation of the E-kios program across various public service facilities, such as the district office. This study aims to analyze the effectiveness of the E-kios program as a form of public service in Benowo District, Surabaya City. This research employs a qualitative descriptive approach, using data collection techniques such as in-depth interviews, direct observation, and document analysis. Informants in this study include district service staff, E-kios operational officers, and members of the public who use the services. The focus of this study is to analyze the extent to which the implementation of the E-kios Program is effective as an innovation in public service delivery in Benowo District, Surabaya City. This study uses five e-government effectiveness indicators, namely: Productivity, the program has had a positive impact on improving services; however, regular public outreach and increased community capacity to use digital services are still needed. Quality, The program has succeeded in improving the speed, efficiency, and convenience of public services. Nonetheless, challenges remain in technical, managerial, and community readiness aspects. Efficiency, The program has been running effectively. Flexibility, The level of flexibility is fairly high, as the system enables residents to access various administrative services without having to visit central service offices directly. Satisfaction, The program shows a high level of user satisfaction, although some technical issues still frequently occur. The research findings indicate that, overall, the E-kios Program has been quite effective in enhancing the accessibility and efficiency of public services in Benowo District. Nevertheless, some challenges in its implementation remain. Based on these findings, the researcher offers the following suggestions: 1.) Increase public outreach and education regarding the program, 2.) Provide training for the community on how to use E-kios, 3.) Improve the quality of E-kios units.